Percepatan Pembangunan Infrastruktur Terhadap Pengembangan Permukiman Berbasis Komunitas Di Kabupaten Jayawijaya Provinsi Papua Indonesia - aprianto soni; Sabriani Sabriani; Warsa Sugandi Karman (Universitas Prof. Dr. Hazairin, S.H, 2022)
The economy is a related subject that largely determines how resources will be allocated. The main focus in this paper is to determine the effect of infrastructure development on the development of community-based settlement development in the area of ??the journal literature review. Based on a literature review of several journals published in the last 5 years with related titles so as to produce and find and model an infrastructure development problem that has an influence on settlement development in improving the economy in a region. Infrastructure seems to be the answer to the needs of countries that want to boost economic growth, by helping reduce poverty, improve the quality of life, support the growth of economic centers and increase the mobility of goods and services and lower the costs of activities of domestic and foreign investors. settlement development on such a basis must be supported by appropriate infrastructure so that development and development are in line with the wishes of various stakeholders. By developing community-based settlement trends.